Cyclophosphamide pharmacokinetics and pharmacogenetics in children with B-cell non-Hodgkin's lymphoma. (March 2016) - Veal, Gareth J.; Cole, Michael; Chinnaswamy, Girish; Sludden, Julieann; Jamieson, David; Errington, Julie; Malik, Ghada; Hill, Christopher R.; Chamberlain, Thomas; Boddy, Alan V.
Abstract: Introduction: Variation in cyclophosphamide pharmacokinetics and metabolism has been highlighted as a factor that may impact on clinical outcome in various tumour types. The current study in children with B-cell non-Hodgkin's lymphoma (NHL) was designed to corroborate previous findings in a large prospective study incorporating genotype for common polymorphisms known to influence cyclophosphamide pharmacology. Methods: A total of 644 plasma samples collected over a 5 year period, from 49 B-cell NHL patients ≤18 years receiving cyclophosphamide (250 mg/m 2 ), were used to characterise a population pharmacokinetic model. Polymorphisms in genes including CYP2B6 and CYP2C19 were analysed. Results: A two-compartment model provided the best fit of the population analysis. The mean cyclophosphamide clearance value following dose 1 was significantly lower than following dose 5 (1.83 ± 1.07 versus 3.68 ± 1.43 L/h/m 2, respectively; mean ± standard deviation from empirical Bayes estimates; P < 0.001). The presence of at least one CYP2B6*6 variant allele was associated with a lower cyclophosphamide clearance following both dose 1 (1.54 ± 0.11 L/h/m 2 versus 2.20 ± 0.31 L/h/m 2, P = 0.033) and dose 5 (3.12 ± 0.17 L/h/m 2 versus 4.35 ± 0.37 L/h/m 2, P = 0.0028), as compared to homozygous wild-type patients. No pharmacokinetic parameters investigated were shown to have a significant influence on progression free survival. Conclusion: The results do not support previous findings of a link between cyclophosphamide pharmacokinetics or metabolism and disease recurrence in childhood B-cell NHL. While CYP2B6 genotype was shown to influence pharmacokinetics, there was no clear impact on clinical outcome. Highlights: The influence of cyclophosphamide clinical pharmacology on childhood cancer outcome has been investigated The presence of at least one CYP2B6*6 variant allele was associated with a lower rate of cyclophosphamide clearance Pharmacokinetic parameters investigated were not shown to have a marked influence on clinical outcome Findings do not support a link between cyclophosphamide metabolism and disease recurrence in B-cell non-Hodgkin's lymphoma